(untitled) (Journal of the College of Basic Education, 2024)
Road advertising is a source of information about items of different shapes, which contains information about a specific product, especially since most products use advertising to promote their products. He had the following question: How is the digital image used in outdoor road advertising? The research reached a set of results: - Traffic advertising that uses digital images stimulates and greatly arouses consumer attention towards the displayed product. - Display advertising that uses digital images is an excellent way to increase the number of consumers for the product and build new customers - Traffic advertising that uses a larger digital image is more attention-grabbing due to its large size. Mobile road advertisements have proven their worth and are more successful than fixed road advertisements.